Recipes and experimentation? The transmission of glassmaking techniques in Medieval Iberia. Issue 2 (2nd July 2016) - Govantes-Edwards, David J.; Duckworth, Chloë N.; Córdoba, Ricardo
ABSTRACT: This paper explores the potential of a combined historical and archaeological approach to the study of glass production in the Iberian Peninsula in the Late Middle Ages. The historical study of technical recipes compiled during the Late Middle Ages and the Early Modern period and the compositional analysis of archaeological material offer different, but equally valuable, insights into glass production. The methodologies, potential and limitations of these techniques are summarised, and their combined use explored, with reference to a fifteenth-century letter written by one Cristóforo de Soto Mayor, its experimental reconstruction, and the comparison of these results with real archaeological datasets.